Is Treatment with Denosumab Associated with Local Recurrence in Patients with Giant Cell Tumor of Bone Treated with Curettage? A Systematic Review. Issue 5 (May 2020) - Tsukamoto, Shinji; Tanaka, Yuu; Mavrogenis, Andreas F.; Kido, Akira; Kawaguchi, Masahiko; Errani, Costantino
Abstract: Background: Denosumab, a monoclonal antibody that binds to receptor activation of nuclear factor-kappa ß ligand (RANKL), has been used as a drug to treat aggressive giant cell tumors of bone. It is unclear whether preoperative denosumab therapy is associated with the local recurrence risk in patients with giant cell tumors of bone treated with curettage. Early evidence suggests that denosumab treatment is associated with a reduction in local recurrence, but other studies have questioned that premise. Curettage after a short course of denosumab (3 to 4 months) has been recommended, especially for large, aggressive giant cell tumors in which complete curettage is difficult to achieve. No randomized studies have documented the benefit of this approach, and some investigators have reported higher local recurrence after denosumab treatment. Due to this confusion, we performed a systematic analysis of existing reports to attempt to answer this question and determine whether the appropriate preoperative denosumab therapy duration could be established. Questions/purposes: (1) Is the use of preoperative denosumab associated with local recurrence risk in patients with giant cell tumors of bone treated with curettage compared with those treated with curettage alone? (2) Is the preoperative denosumab therapy duration associated with local recurrence after curettage? Methods: We searched the PubMed, EMBASE, and CENTRAL databases on April 26, 2019 and included both randomized and non-randomized studies that compared local recurrence between patients who had giant cell tumors of bone and were treated with curettage after preoperative denosumab and patients treated with curettage alone. Two authors independently screened the studies. There were no randomized studies dealing with denosumab in giant cell tumors of bone, and generally, denosumab was used for more aggressive tumors. We assessed the quality of the included studies using the Risk of Bias Assessment tool for Non-randomized Studies, with a moderate overall risk of bias. We registered our protocol in PROSPERO (registration number CRD42019133288). We selected seven eligible studies involving 619 patients for the final analysis. Results: The proportion of patients with local recurrence ranged from 20% to 100% in the curettage with preoperative denosumab group and ranged from 0% to 50% in the curettage-alone group. The odds ratio of local recurrence ranged from 1.07 to 37.80 in no more than 6 months of preoperative denosumab duration group and ranged from 0.60 to 28.33 in more than 6 months of preoperative denosumab duration group. Conclusions: The available evidence for the benefit of denosumab in more aggressive giant cell tumors is inconclusive, and denosumab treatment may even be associated with an increase in the proportion of patients experiencing local recurrence. Because there are no randomized studies and the existing studies are of poor quality due to indication bias (the most aggressive Campanacci 3 lesions or those where even a resection would be difficult and result in morbidity are generally the patients who are treated with denosumab), the evidence to suggest a disadvantage is weak. Denosumab treatment should be viewed with caution until more definitive, randomized studies documenting a benefit (or not) have been conducted. Furthermore, we could not find evidence to suggest an appropriate length of preoperative denosumab before curettage.